Computerised infrared thermography and isotopic bone scanning in tennis elbow. Issue 1 (January 1992) - Thomas, D; Siahamis, G; Marion, M; Boyle, C
Abstract : Thirty five cases of tennis elbow (17 unilateral, nine bilateral) were studied with infrared thermography and isotopic bone scanning. A hot focus was visualised in 16 of 17 cases of unilateral tennis elbow (94%) and in all nine cases of bilateral tennis elbow (100%) on infrared thermography, and abnormal increased epicondylar activity seen in 12 of 17 (71%) and eight of 18 (44%) cases respectively with isotopic bone scanning. Unilateral visual cooling (somatosympathetic responses) occurred in seven of 13 cases of unilateral tennis elbow (54%) with infrared thermography, and reduced perfusion in seven of 12 (58%) of similar cases with blood pool isotopic bone scanning. Computerised temperature assessments showed statistically significant side to side temperature differences when 17 active tennis elbows were compared with the opposite normal elbows for spot temperatures, proximal and distal forearm gradients. Similar temperature assessments in 18 bilateral tennis elbows compared with 17 normal elbows showed significant temperature differences for elbow spot temperatures and distal forearm gradients, but not for proximal gradients.